The Bombshell Cello - Khabat Abas (Parse Journal, 2022)
This video essay records a process of constructing a new cello out of a bombshell found in the bazaar of Sulaymaniyah City in Iraq. The work gave rise to an experimental musical practice as well as to inquiries about aspects of agency evolving from the “dance” between performer and material—between a body that carries a personal history and the traces of change from violent to cultural material. New instrumental techniques are being developed producing timbres one would not expect from an ordinary cello. Sound may be described as a soft power that affects our vision and taste, whereby listening allows us to see without using our eyes. The essay captures one individual’s experience of the hidden side of war, and through listening invites an audience to consider how war shapes both society and individuals.